PENGARUH ETIKA, KAPASITAS KERJA DAN KEMAMPUAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN PIDIE - Cut Maitriani; Rosda Novita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
This study aims to determine the effect of ethics, work capacity, work ability and the more dominant variables on the work productivity of the Pidie Regency Population and Civil Registry Office employees. The research population was all employees of the Population and Civil Registry Office of Pidie Regency, as many as 70 people. Data collection techniques consist of observation, interviews and questionnaires. Data analysis using multiple linear regression equation = a + b1X1+ b2X2 + b3X3 + e. The results of data analysis obtained a linear regression equation model as follows: Y = 1.709+ 0.297X1+ 0.271X2 + 0.399X3. The Work Ability Variable (X3) has the most dominant influence on the productivity of the Population and Civil Registry Office of Pidie Regency. The index of determination of the Ethics variable (X1), Work Capacity (X2), and Work Ability (X2) is 56.1% while the remaining 43.9% is influenced by other variables not examined in this study. Simultaneously, the value of Fcount 28,072 Ftable 2,744, which means that the variables of Ethics (X1), Work Capacity (X2) and Work Ability (X3) together have a significant effect on the Productivity of the Population and Civil Registry Office of Pidie Regency. The Ethics variable (X1) has a tcount value of 3,506 ttable 1,955, which means that partially the Ethics variable (X1) has a significant effect on the work productivity of the Population and Civil Registry Office of Pidie Regency. Work Capacity Variable (X2) obtained t count 3.461 t table 1.955, which means that partially the Work Capacity variable has a significant effect on the work productivity of the Pidie Population and Civil Registry Office employees. Workability variable (X3) is obtained tcount 4. 409 ttable 1,955, which means that partially the Workability variable has a significant effect on the work productivity of the Pidie Regency Population and Civil Registry Office employees. It is hoped that the employees of the Population and Civil Registry Office of Pidie Regency will further increase work productivity through improving work ethics and abilities.Keywords: Ethics, Work Capacity, Work Ability, Work Productivity